IMPROVING STUDENTS' LISTENING ABILITIES USING THE LISTEN-WRITE METHOD IN THE INDONESIAN LANGUAGE SUBJECT FOR FOURTH GRADE ELEMENTARY SCHOOL - Rahmad Wahyuddin (Edelweiss : Journal Of Innovation In Educational Research, 2026)
This study aimed to enhance fourth-grade elementary students' listening abilities in the Indonesian Language subject through the implementation of the Listen-Write method during the academic year 2025/2026 in Tanjung Pura District. Employing Classroom Action Research (CAR) with two cycles, the research addressed initial deficiencies observed in preliminary assessments, where the average listening score was 60.5, with only 40% of the 30 students meeting the passing criterion of 75. The Listen-Write method involved students listening to audio materials and immediately transcribing key elements, followed by discussions to reinforce comprehension. In Cycle 1, adjustments focused on structured note-taking, resulting in an average score of 72.3 and 70% passing rate. Reflections led to refinements in Cycle 2, such as simplified audio and peer support, yielding an average score of 85.6 and 90% passing rate, marking a 41.5% overall improvement. Qualitative data from observations and field notes indicated increased engagement, focus, and motivation. The findings confirm the method's effectiveness in promoting active learning and multisensory retention, offering practical implications for elementary language education. Recommendations include broader adoption and further studies on long-term effects in diverse contexts.